Electropolymerized phenol derivatives as permselective polymers for biosensor applications1. Issue 10 (21st May 2015) - Calia, Giammario; Monti, Patrizia; Marceddu, Salvatore; Dettori, Maria A.; Fabbri, Davide; Jaoua, Samir; O'Neill, Robert D.; Serra, Pier A.; Delogu, Giovanna; Migheli, Quirico
<x xml:space="preserve">Abstract</x> Amperometric biosensors are often coated with a polymeric permselective film to avoid electroactive interference by reducing agents present in the target medium.